Analisis Penerapan PPh Pasal 23 atas Jasa di PT WB Majalengka - Raras Putri Utami (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the application of Income Tax (PPh) Article 23 on services at PT WB Plant Majalengka. The method used is descriptive qualitative with a case study approach through observation, interviews, and tax document analysis. The results show that the implementation of PPh Article 23 is in accordance with applicable tax regulations, including proper tax object classification, application of a 2% rate for vendors with NPWP, and DPP determination excluding VAT. The administrative process runs systematically and reporting is conducted on time. However, several constraints were identified, such as dependence on accounting data readiness, technical issues in the Coretax DJP system, and incomplete electronic withholding certificates. Therefore, improvements in internal scheduling, document verification, and inter-unit coordination are recommended. These findings are expected to serve as a reference for companies in optimizing tax compliance and strengthening the internal control system in managing PPh Article 23 obligations.